«Let’s remember everyone by name»: reflecting on the martyrology of the victims of Civil War in Omsk region - V. V. Kalinovsky (Омский научный вестник: Серия "Общество. История. Современность")
The paper provides an analytical review of the scientific reference publication «Victims of the Civil War: a reference book-martyrology on the act records of the parish registers of the temples of the Omsk region (June 1918–December 1919)», prepared by the creative team of Omsk historians-archivists — candidates of historical sciences Dmitry Igorevich Petin and Maxim Maksimovich Stelmak. The features of the author’s approach, chosen as key criteria in the preparation of the publication, are critically comprehended. The use of a theoretical set, consisting of the principle of consistency, problematic and comparative historical methods, allows us to present the analyzed work as a striking phenomenon of historical science. The general scientific, cultural and methodological novelty of the publication is noted.